KAJI EKSPERIMENTAL CIRI GETARAN PADA BANTALAN ROL DENGAN PEMBEBANAN STATIK - K Magiano; Komang Bagiasna (Mesin, 2009)
Any rolling bearing defect has a certain vibration response signature which can be observed through its waveform as well as frequency spectrum, such as the sideband frequencies, which indicate there is modulation phenomena among the vibration response signals. This research was carried out to study the vibration response signatures in the roll bearings due to the interaction between the static load and bearing inner/outer race waviness. This experimental research consists of FRF (Frequency Response Function) measurements to obtain the dynamic characteristics of the rolling bearing vibration, and power spectrum testing to measure the vibration response that occurs in the bearing. The shaft speed and static loads (vertical, horizontal, combination) are varied during the experimental study. Experimental results reveal Roll Passage Frequency (RPF) and its sidebands caused by the static load, and it was also found that waviness in the order of 4 at the inner race and in the order of 6 at the outer race of the bearing.